Application of astatine-210: Evaluation of astatine distribution and effect of pre-injected iodide in whole body of normal rats. (September 2018) - Ikeda, Hayato; Hayashi, Yoshihiko; Takahashi, Naruto; Watabe, Tadashi; Kanai, Yasukazu; Shinohara, Atsushi; Kato, Hiroki; Watabe, Hiroshi; Shimosegawa, Eku; Hatazawa, Jun
Abstract: We proposed use of astatine-210 in preclinical study. Astatine-210 has higher yield of production and is easier to quantify than astatine-211. We produced astatine-210 with Bi target and 40 MeV alpha beam accelerated by cyclotron, free astatine-210 was separated and injected to normal rats. Three male rats (blocking group) were injected non-radioactive iodide before injection of astatine-210. Compared with the control group, the astatine-210 accumulations in the blocking group decreased to 24% in the thyroid. Highlights: Free 210 At was administered to normal rats instead of free 211 At. The pre-injection of I- reduced the accumulation of 210 At in the thyroid and stomach. We estimated the behavior of 211 At based on the biodistribution of 210 At.